2009
DOI: 10.1071/cp08253
|View full text |Cite
|
Sign up to set email alerts
|

Yield determination in olive hedgerow orchards. II. Analysis of radiation and fruiting profiles

Abstract: Profiles of fruit density, fruit size, and oil content were measured on 12 occasions in 7 olive orchards in Spain and 2 in Australia. Orchard structure varied widely. Height ranged from 2.0 to 5.5 m, row spacing from 3 to 6 m, and canopy width from 0.7 to 3 m. Most orchards were oriented north-south (N-S) but one in Spain was oriented close to east-west (E-W) (208 NE-SW). All orchards in Spain were cv. Arbequina, and in Australia they were cvv. Barnea and Picual. Analyses with a model of interception and trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 16 publications
3
45
0
Order By: Relevance
“…In E-W hedgerows, the differences between S and N sides were more evident in the most closely spaced rows. This response can be attributed to reduced transmission of radiation from sunlit S to shaded N sides as row spacing decreases even if, as previously suggested (Connor et al, 2009), lower threshold values of irradiance for fruit formation and development in olive, might increase productivity on the N side of closely spaced E-W hedgerows.…”
Section: Hedgerow Productivitymentioning
confidence: 79%
See 1 more Smart Citation
“…In E-W hedgerows, the differences between S and N sides were more evident in the most closely spaced rows. This response can be attributed to reduced transmission of radiation from sunlit S to shaded N sides as row spacing decreases even if, as previously suggested (Connor et al, 2009), lower threshold values of irradiance for fruit formation and development in olive, might increase productivity on the N side of closely spaced E-W hedgerows.…”
Section: Hedgerow Productivitymentioning
confidence: 79%
“…This response is consistent with greater irradiance on S sides in more widely spaced hedgerows and greater transmission through to N sides with consequently more even distribution of irradiance within both sides of widely spaced E-W hedgerows, depending upon porosity. Fruit oil content was similar between S and N sides at each height in all row spacings, a likely explanation being that oil accumulation occurs mainly in autumn when transmission from illuminated S to shadowed N side increases (Connor et al, 2009).…”
Section: Vertical Distribution Of Oil Yield Components In Either Sidementioning
confidence: 96%
“…• Orchards are oriented N-S, because previous work has shown that the relationships are not applicable to asymmetrically illuminated E-W orchards (Connor et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…This is a reasonable assumption for N-S canopies of 0.7-m width or more, even those with a horizontal porosity of 15-20%. This arises because the trajectory of sunlight through the hedgerows is sufficiently long for almost complete interception diurnally (Connor et al, 2009). Further, since N-S hedgerows are illuminated equally on each side during the day, radiation passing through to the other side of the hedgerow before noon is compensated, on a daily basis, by complementary interception afterwards.…”
Section: Terminologymentioning
confidence: 99%
See 1 more Smart Citation